Primerjava testov ponavljajocih se šprintov pri mladih nogometaših: naravnost proti cikcak - Alemdaroglu, U.; Köklü, Y.; Bektas, F.; Celik, G.; Ünver, F.; Duffield, R. (Kinesiologia Slovenica, 2018)
The purpose of this study was to compare the differences between physiological and performance response to different repeated sprint tests (RSTs). Nine young soccer players (age 18.3 ± 1.0 years; height 176.8 ± 5.0 cm; body-mass 74.1 ± 6.9 kg) performed Yo-Yo Intermittent Recovery Test Level 1 (YIRT1), Wingate Anaerobic Test (WAnT) and four different RST`s; including two straight tests (6 x 40 m, and 8 x 30 m) and shuttle tests (6 x 40 m and 8 x 30 m) maximal runs starting every 25s. Blood lactate (La-) was measured three minutes following each RST. Significantly higher average speed responses were determined from 6 x 40 m straight than other RSTs, Additionally, a strong correlation (r=0.80) was found between the best sprint times for 6 x 40 m and the 8 x 30 m straight RST protocols. Moderate correlations were found between YIRT1 performance and the 8 x 30 m straight test performance (range: r= 0.69 to 0.72) (p=0.05). Moreover, there were significant correlations in the total sprint times of RSTs for all protocols except 8 x 30 m shuttle (range: r= 0.68 to 0.90). Therefore, if coaches want higher speed in their training, they can choose straight RSTs and if they want higher physiological response they may select shuttle RSTs..